Decent work through green jobs in a green economy - Ofreneo, Rene E. (Philippine Journal of Labor and Industrial Relations, 2010)
The Philippine is facing two difficult and intertwined environmental tasks: minimizing the adverse impact of climate change through varied mitigation/adaptation measures and restoring its degraded environment. The way forward for the country is to pursue this tasks with greater vigour, coherence and consistency in the context of the need to green the economy and the labor market. This green economic shift is value-adding, job-creating and a key to the creation of jobs that are both green (promote dignity, security, equity and stability at work).